1974
DOI: 10.1172/jci107632
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effect of 25-Hydroxycholecalciferol on Renal Handling of Phosphorus

Abstract: A B S T R A C T The acute effect of i.v. and direct intrarenal arterial infusion of These results indicate that 25HCC enhances tubular reabsorption of phosphorus in rats, only in the presence of either endogenous or exogenous circulating PTH, but not in its absence and thus imply a PTH-dependent mechanism of 25HCC action on the kidney. This effect does not appear to be related to the conversion of 25HCC into 1,25DHCC, since the latter fails to affect tubular reabsorption of phosphorus in PTX rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
2
2

Year Published

1976
1976
1992
1992

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(19 citation statements)
references
References 26 publications
2
13
2
2
Order By: Relevance
“…In the experiments described in Table 1 Vitamin D3 analog, M dent uptake of phosphate (12) and with reports of others that the acute effect of infusion of 1,25-(OH)2D3 in the intact animal was to decrease phosphate excretion (5,6). The present findings also agree with the previously reported effect of the vitamin in increasing phosphate uptake by organ culture preparations of chick ileum explants and isolated intestinal cells (13,14).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…In the experiments described in Table 1 Vitamin D3 analog, M dent uptake of phosphate (12) and with reports of others that the acute effect of infusion of 1,25-(OH)2D3 in the intact animal was to decrease phosphate excretion (5,6). The present findings also agree with the previously reported effect of the vitamin in increasing phosphate uptake by organ culture preparations of chick ileum explants and isolated intestinal cells (13,14).…”
Section: Methodsmentioning
confidence: 86%
“…The effect of 1,25-(OH)2D3 on the reabsorption of phosphate in the kidney is in dispute. In some studies, infusion of the vitamin has been found to decrease phosphate excretion (5,6), whereas in other investigations 1,25-(OH)2D3 has been reported to be phosphaturic (7) or without effect on urinary phosphate (8). Some of the difficulties in resolving the apparent discrepancies stem, in part, from whether 1,25-(OH)2D3 is administered chronically or acutely and from the complex interactions in the animal in vivo of the vitamin D metabolic and phosphate transport systems with various regulatory factors, including parathyroid hormone and other endocrines, dietary status, and calcium (9)(10)(11).…”
mentioning
confidence: 99%
“…Also, urinary Pi excretion was lower in the 1,25LD or 1,25HD groups for any given level of serum Pi. Popovtzer et al (31) and Puschett et al (32) both reported an antiphosphaturic action of 25(OH)D3 in rats that was dependent upon the presence of parathyroid hormone (PTH). The quantities of 25(OH)D3 utilized in their studies were considerably greater than the amount of vitamin D3 given here and much greater than the amount of 1,25(OH)2D3 employed.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin D (25,26) and its metabolites (26,27), when administered in pharmacologic doses, accelerate Pi reabsorption, although the presence of PTH may be required for such an action in the rat (28). Recently, we have carried out phosphate loading studies in chronic TPTX phosphorus-depleted rats which were also vitamin D-deficient (4 (32).…”
Section: Resultsmentioning
confidence: 99%